Erythema Nodosum Leprosum as a Harbinger of Relapse in Multibacillary Leprosy: A Clinico-Histopathological Case Study - Benedikta Lauda; Nurrachmat Mulianto (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Leprosy, a chronic granulomatous disease caused by Mycobacterium leprae, presents formidable long-term management challenges. In the post-elimination era, differentiating a true bacteriological relapse from a late-onset Erythema Nodosum Leprosum (ENL) reaction in patients who have completed multidrug therapy (MDT) is a critical diagnostic dilemma. Misdiagnosis can lead to inappropriate treatment, risking disease progression and irreversible nerve damage. Case presentation: A 30-year-old male presented with a severe, systemic inflammatory illness two years after completing MDT for lepromatous leprosy. His symptoms included crops of painful, erythematous nodules, fever, and arthralgia. While clinically suggestive of a severe ENL reaction, a slit-skin smear revealed a paradoxically high bacterial index (BI) of +5 with a morphological index (MI) of 0%. A skin biopsy was performed for definitive diagnosis. Histopathology revealed a dual pathology: a diffuse infiltrate of foamy macrophages typical of lepromatous leprosy, alongside a dense neutrophilic panniculitis characteristic of ENL. Crucially, Fite-Faraco staining demonstrated vast numbers of intact, solid-staining acid-fast bacilli, providing unequivocal evidence of active bacterial proliferation. Conclusion: This case demonstrates that a diagnostic algorithm integrating a high index of clinical suspicion with comprehensive bacteriological and histopathological methods is essential for accurately identifying relapse masked by ENL. The presence of viable bacilli confirms that ENL can be a direct clinical harbinger of relapse, mandating a dual therapeutic strategy that combines aggressive anti-inflammatory treatment with the immediate re-initiation of MDT.